Examining the Relationship between Post Primary School Teachers Job Satisfaction and Empowerment on Turnover Intention in Katsina State Nigeria - Abba Yangaiya Salisu (Universitas Mercu Buana, 2020)
The study focuses on the influence of post primary schools teacher’s Job Satisfaction and Empowerment on turnover intention in Katsina state Nigeria. Job Satisfaction Questionnaire (JSQ), Empowerment Questionnaire (EQ) and Turnover Intention Questionnaire (TIQ) were used to get the data used in this study. All the questionnaires were adopted and adapted. The data was analyzed using multiple regression analysis via SPSS version 20.0. The results indicate that the independent variables influences turnover intention of post primary school teachers (R2 .51). In addition, among the independent variables, Job satisfaction best influences turnover intention of post primary school teachers. The results would be useful to the stakeholders as before now few studies were conducted in the area in Nigeria in general and Katsina state in particular.